Molecular Identification of Fungi and Determination of Aflatoxin B1 in Dried Tomatoes - Salisu , N.; Ukwaja , V.C.; Sakariyau , W.A (International Journal of Scientific Research in Biological Sciences, 2023)
Occurrence of fungi and their secondary metabolites such as mycotoxins in tomatoes is of great public health concern. World economies as well as human and animal health are significantly affected by their presence. It is therefore imperative to understand the species of fungi and the types of mycotoxins produced by them. This study is aimed at isolating, characterizing, and comparing the fungal load as well as quantifying aflatoxin B1 levels produced in dried tomatoes sold within Gusau metropolis. A total of 23 tomato samples were randomly obtained from different markets in the study area. Of the samples, 39 fungal isolates were found; three of the fungal isolates belong to the genus Aspergillus. Aspergillus flavus, which is known largely for the production of aflatoxins, was identified as the predominant occurring fungus with 48.7% (n = 19), and the least occurring fungi were Curvularia americana and Fomitoptis maliae with 2.6% (n = 1) each. The rRNA gene of the isolates was amplified by PCR and sequenced. The sequence data were deposited in the NCBI database, and accession numbers were assigned to each isolate. Aflatoxin B1 (AFB1) was detected and quantified from the samples, and findings from this study indicated that AFB1 was present in all the samples analyzed. Also, 43.48% of the samples exceeded the maximum permissible number of 20 µg/kg set by the Standard Organization of Nigeria. In general, this result suggests that the presence of AFB1 in all the samples confirmed that Aspergillus flavus is the highest aflatoxins-producing fungus. It is therefore recommended that food products be screened for the types of fungal species and the presence of mycotoxins for food and public health safety.